Scattering from a dielectric cylinder partially buried in a dielectric half space with a periodic height profile by a decomposition method - Saynak, U.; Kizilay, A. (TAYLOR & FRANCIS LTD, 2019)
A new solution method is applied to solve the problem of electromagnetic scattering partially buried dielectric cylinder at the dielectric rough surface interface. The rough interface is chosen to be infinitely long and periodic with arbitrary profile. Equivalency principle is used to obtain a set of electric field integral equations (EFIEs) for the currents on the scattering object surface and the perturbation currents on a finite portion of interface near the object. The Method of Moments is used to solve the EFIEs in the frequency domain to obtain the scattered field. The method is presented with examples for TM polarization.
Keywords: Electromagnetic wave scattering; Method of Moments; computational electromagnetics; equivalency principle; SOMMERFELD INTEGRALS; PEC CYLINDER; INTERFACE; SURFACE; COMPUTATION; EXCITATION; FIELDS; Engineering; Physics